An Analysis on Online Shopping Based on Fuzzy Logic: A Review Perspective: Analyzing the Impact of Fuzzy Logic on Customer Attitudes and Satisfaction in Online Shopping (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Online Shopping has become a more preferred option as the Internet is a daily requirement for people nowadays. Due to its convenience, handiness, and anytime and anywhere shopping, variety of products, and numerous discounts and deals on goods, online shopping is the most favored choice for customers. The focus of this new era of e-commerce is on understanding the perception of consumers towards online shopping. A lot of studies have been done to learn more knowledge about this ever-evolving sector. The goal of this paper is to get an idea of the attitudes of the customers towards shopping online about their growth regarding online shopping, artificial intelligence in E-commerce, and their technology. This paper outlines the numerous components that have a moderating effect on loyalty, e-marketing, customer satisfaction, and appreciated value. In view of the scope and diversity of the customers, e-marketing must continue to be crucial for the unique market.Online platforms continue to be important because of the reach and the diversity of the customers meaning e-marketing should target the unique market. Online customer reviews to test customer reviews performance. The technique pre-processes the text of the input using fuzzification and defuzzification and then uses the fuzzy logic of decision-making.